Ansel Adams [videorecording (DVD)] : a documentary film - Burns, Ric; Stiers, David Ogden; Hamilton, Josh; Feldon, Barbara; Wallach, Eli, 1915-2014 (PBS Home Video ; Distributed by Paramount Home Entertainment, 2004)
Few American artists have reached a wider audience or enjoyed more widespread popularity in their own lifetime than Ansel Adams. Ansel Adams had a profound impact on how Americans see the majesty or their continent and helped transform how people think and feel about the meaning of the natural world. A visionary photographer, a pioneer in photographic technique and a crusader for the environment, this portrait of Adams portrays the great artist and ardent environmentalist.